Peran Ambiguity Confusion dalam Word of Mouth pada Platform Marketplace - Hidayah, Nur (J-MIND (Jurnal Manajemen Indonesia), 2021)
Â This study is an case study that aims to analyze the effect of ambiguity confusion on word of mouth. The type of data used in this study is primary data from platfom marketplace user. The number of samples in this study were 150 user that selected by purposive sampling method. The independent variable used is ambiguity confusion, while dependent variable is word of mouth. The analysis model used in this research is multi linear regression analysis using SPSS 25. The result show that the ambiguity has positive effect on word of mouth.Â